Should intra-familial time transfers be compensated financially? - Nataliya Kusa (Philipps-University Marburg, School of Business and Economics, 2018)
This paper deals with social acceptance of applying the equity principle for intra-familial time transfers. Based on a representative survey among German citizens, the author provides empirical evidence on acceptance of financial compensation for different time transfers. Some 80% of the subjects stated that intra-familial long-term care should be compensated. At the same time, only 38% of subjects stated that grandparental childcare should be compensated: The majority accepts equity principle for intra-familial long-term care but not for grandparental childcare. Age has the strongest effect: subjects belonging to the old generation are more likely to accept the equity principle for informal long-term care as well as for grandparental childcare. Family valuation does not matter in any of the dimensions. It is puzzling that being a female by itself does not explain the differences in social acceptance even though females are much more actively involved in all types of time transfers.
Keywords: D31; D63; D64; 330; intergenerational transfers; long-term care; grandparental childcare; citizens' view; equity